2014
DOI: 10.3748/wjg.v20.i42.15632
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immunity and inflammatory gene expression in the gut, in inflammatory diseases of the gut and in the liver by probiotics

Abstract: The potential for the positive manipulation of the gut microbiome through the introduction of beneficial microbes, as also known as probiotics, is currently an active area of investigation. The FAO/WHO define probiotics as live microorganisms that confer a health benefit to the host when administered in adequate amounts. However, dead bacteria and bacterial molecular components may also exhibit probiotic properties. The results of clinical studies have demonstrated the clinical potential of probiotics in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 105 publications
3
123
0
2
Order By: Relevance
“…Proinflammatory cytokines such as TNF-a and IL-1b mediate powerful inflammatory responses of fish after infection [14], while antiinflammatory cytokines such as TGF-b and IL-10 exert potent immunosuppressive effects predominantly through their multiple effects on T cells and B cells [62]. A number of probiotics can effectively modulate the expression of pro-and anti-inflammatory cytokines in many animals [14,18]. In this study, mRNA changes of the above cytokine genes in intestine were detected after oral administration of the spores of B. subtilis strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines such as TNF-a and IL-1b mediate powerful inflammatory responses of fish after infection [14], while antiinflammatory cytokines such as TGF-b and IL-10 exert potent immunosuppressive effects predominantly through their multiple effects on T cells and B cells [62]. A number of probiotics can effectively modulate the expression of pro-and anti-inflammatory cytokines in many animals [14,18]. In this study, mRNA changes of the above cytokine genes in intestine were detected after oral administration of the spores of B. subtilis strains.…”
Section: Discussionmentioning
confidence: 99%
“…One is the competition between species: probiotics adhered to the intestinal mucosal surface can prevent the colonization of pathogenic bacteria, and alter the composition of the intestinal microbiota in animals [13]. Another is the stimulating of the intestinal immune system via the modulation of cytokine levels [14]. In addition, probiotics promote growth rate through producing enzymes, vitamins, and mineral supplements, which help to improve digestion and nutrients absorption [5].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between beneficial commensal bacteria and the immune cells results in a downregulation of proinflammatory genes, whereas anti-inflammatory genes are upregulated. 29,30 Although identification of the microbiota is ongoing in the Human Microbiome Project, the majority of GI microbiota is still uncharacterized. It is now certain that it consists of a great variety of microbes with a majority of anaerobic bacteria.…”
Section: Ibsmentioning
confidence: 99%
“…The mechanism by which these strains inhibited the LPS-stimulated release of inflammatory mediators from the host cells has not been elucidated and warrants investigation in future studies. However, previous research has shown that probiotic strains used in the gut can interact with toll-like receptors on host cells to downregulate the expression of nuclear factor-kappa-B and proinflammatory cytokines [25]. …”
Section: Discussionmentioning
confidence: 99%